The Effects of A 6-Week Plyometric Training Programme on Sand Versus Wooden Parquet Surfaces on the Physical Performance Parameters of Well-Trained Young Basketball Players - Gokmen Ozen; Ozdemir Atar; Hurmuz Koc (Montenegrin Sports Academy, 2020)
The purpose of this study was to investigate the effect of plyometric training on sand and wooden parquet training surfaces on the physical performance parameters of young male basketball players. Twelve well-trained young male basketball players with age 17.58±0.5 years, body mass 87.73±9.82 kg, and height 193.75±7.02 cm were voluntarily involved in the study. All participants were grouped randomly as sand and wooden training groups. A six-week plyometric training programme was performed on the sand and wooden parquet surfaces. Anthropometric measurements and physical performance tests; vertical and standing long jump, box agility, and 30m sprint tests were performed. Data were collected before and after six weeks of plyometric training and were analysed using ANCOVA. The results indicated that the plyometric training programme significantly improved jumping, agility and 30m sprint performance for both groups. Significant differences were found between the post-test mean values of two groups in the box-drill agility and 30m sprint test scores (p < .05). The results of this study suggest that while the plyometric training performed on a wooden or sand surface does not cause a different effect on the improvement of jumping performance, plyometric training on the sand surface may be a more effective training surface to improve the agility and sprint performance of young players.